Bis(2-acetyl-5-hydroxyphenolato-κ2O,O′)copper(II) - Ali, Hapipah Mohd; Ng, S.W.; Halim, S.N.A. (International Union of Crystallography, 2005)
The Cu atom in the title compound, [Cu(C8H7O 3)2], lies on a center of inversion and exists in a square-planar enviroment that is defined by the four chelating O atoms. Intermolecular O-H⋯O hydrogen bonds [O⋯O = 2.711 (3)Å] link adjacent molecules into a layer structure. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.